2016
DOI: 10.1073/pnas.1605477113
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of a dehydratase important for intracellular growth and cording renders rough Mycobacterium abscessus avirulent

Abstract: Mycobacterium abscessus (Mabs) is a rapidly growing Mycobacterium and an emerging pathogen in humans. Transitioning from a smooth (S) high-glycopeptidolipid (GPL) producer to a rough (R) low-GPL producer is associated with increased virulence in zebrafish, which involves the formation of massive serpentine cords, abscesses, and rapid larval death. Generating a cord-deficient Mabs mutant would allow us to address the contribution of cording in the physiopathological signs of the R variant. Herein, a deletion mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 60 publications
2
66
0
Order By: Relevance
“…Since previous TAC analogues were found to be more efficient against M. avium (16) and M. tuberculosis (19), we were prompted to address whether TAC analogues also exhibit potent activity against M. abscessus, notorious for being the most drug-resistant mycobacterial species (21), despite being refractory to TAC inhibition in liquid cultures (MIC of Ͼ100 g/ml) (18). As shown in Table 1, the compounds exhibited a broad range of activity against the rough (R) variant of M. abscessus CIP104536, from active compounds (Ͻ10 g/ml) to derivatives exhibiting only modest (Ͻ50 g/ml) or very poor activity (Ն100 g/ml).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since previous TAC analogues were found to be more efficient against M. avium (16) and M. tuberculosis (19), we were prompted to address whether TAC analogues also exhibit potent activity against M. abscessus, notorious for being the most drug-resistant mycobacterial species (21), despite being refractory to TAC inhibition in liquid cultures (MIC of Ͼ100 g/ml) (18). As shown in Table 1, the compounds exhibited a broad range of activity against the rough (R) variant of M. abscessus CIP104536, from active compounds (Ͻ10 g/ml) to derivatives exhibiting only modest (Ͻ50 g/ml) or very poor activity (Ն100 g/ml).…”
Section: Resultsmentioning
confidence: 99%
“…Upon activation, TAC has recently been shown to bind to the HadA component of the HadABC dehydratase complex, leading to inhibition of mycolic acid biosynthesis (15). Interestingly, we and others have reported that NTM such as Mycobacterium avium (16), Mycobacterium smegmatis (17), and M. abscessus (18) are naturally resistant to TAC. However, a TAC analogue, SRI-224, was previously tested against M. avium and found to be more effective than TAC in vitro as well as in mice (16) and subsequently shown to be very active against M. tuberculosis (19).…”
mentioning
confidence: 97%
“…Indeed, although representing an emerging human pathogen involved in pulmonary and cutaneo‐mucous infections, M. abscessus is endowed with metabolic pathways typically found in environmental microorganisms that are in contact with soil, plants and aquatic environments (Ripoll et al ., ) where free‐living amoebae are present. We and others have recently shown that M. abscessus can survive in amoebae (Drancourt, ; Bakala N'Goma et al ., ; Halloum et al ., ). Interestingly, amoebae such as Dictyostelium have been shown to build up their own lipid bodies when presented with palmitic acid (Du et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, a Mabs R mutant defective in cording showed severely impaired replication in both macrophages and amoebae, presumably due to limited inhibition of the phagolysosomal fusion. These studies emphasize the usefulness of amoebae as a host model to identify and study determinants important in sustaining Mabs virulence (Halloum et al, 2016). Despite the failure of isolating Mabs from environmental sources, studies with Acanthamoeba suggest that Mabs has evolved in close contact with environmental protozoa and support the view that amoebae contribute in shaping Mabs virulence (Bakala N'Goma et al, 2015; Le Moigne et al, 2016).…”
Section: Introductionmentioning
confidence: 91%
“…This has led to the recent identification of the MAB_4780 gene encoding a dehydratase. Disruption of this gene in Mabs R was associated with the lack of granuloma formation in embryos and a highly attenuated phenotype in wild-type and in embryos lacking either macrophages or neutrophils (Halloum et al, 2016). Overall, work using the zebrafish model confirmed the crucial role of MAB_4780 for Mabs cording to successfully establish acute and lethal infections.…”
Section: Introductionmentioning
confidence: 99%